Central nervous system medication use in older adults with intellectual disability: Results from the successful ageing in intellectual disability study. (April 2016) - Chitty, Kate M; Evans, Elizabeth; Torr, Jennifer J; Iacono, Teresa; Brodaty, Henry; Sachdev, Perminder; Trollor, Julian N
Objective: Information on the rates and predictors of polypharmacy of central nervous system medication in older people with intellectual disability is limited, despite the increased life expectancy of this group. This study examined central nervous system medication use in an older sample of people with intellectual disability. Methods: Data regarding demographics, psychiatric diagnoses and current medications were collected as part of a larger survey completed by carers of people with intellectual disability over the age of 40 years. Recruitment occurred predominantly via disability services across different urban and rural locations in New South Wales and Victoria. Medications were coded according to the Monthly Index of Medical Specialties central nervous system medication categories, including sedatives/hypnotics, anti-anxiety agents, antipsychotics, antidepressants, central nervous system stimulants, movement disorder medications and anticonvulsants. The Developmental Behaviour Checklist for Adults was used to assess behaviour. Results: Data were available for 114 people with intellectual disability. In all, 62.3% of the sample was prescribed a central nervous system medication, with 47.4% taking more than one. Of those who were medicated, 46.5% had a neurological diagnosis (a seizure disorder or Parkinson's disease) and 45.1% had a psychiatric diagnosis (an affective or psychotic disorder). Linear regression revealed that polypharmacy was predicted by the presence of neurological and psychiatric diagnosis, higher Developmental Behaviour Checklist for Adults scores and male gender. Conclusion: This study is the first to focus on central nervous system medication in an older sample with intellectual disability. The findings are in line with the wider literature in younger people, showing a high degree of prescription and polypharmacy. Within the sample, there seems to be adequate rationale for central nervous system medication prescription. Although these data do not indicate non-adherence to guidelines for prescribing in intellectual disability, the high rate of polypharmacy and its relationship to Developmental Behaviour Checklist for Adults scores reiterate the importance of continued medication review in older people with intellectual disability.